General System of A-Monotone Nonlinear Variational Inclusions Problems with Applications. (3rd November 2009) - Peng, Jian-Wen; Zhao, Lai-Jun
Abstract : We introduce and study a new system of nonlinear variational inclusions involving a combination ofA -Monotone operators and relaxed cocoercive mappings. By using the resolvent technique of theA -monotone operators, we prove the existence and uniqueness of solution and the convergence of a new multistep iterative algorithm for this system of variational inclusions. The results in this paper unify, extend, and improve some known results in literature.